Hyperostosis frontalis interna: A new perspective in burned individuals' analysis for determining age and sex from archeo‐anthropological and medicolegal contexts. (15th November 2022) - Du Fayet de la Tour, Anaïs; Couture, Christine; Paraf, François; Duday, Henri
Abstract: Hyperostosis frontalis interna (HFI) is a benign bone lesion, which is asymptomatic for the most part and is manifested by the accretion of bone on the endocranial surface of the frontal bone. This type of lesion has been discussed in a multitude of publications since the 19th century. Although a consensus has yet to be reached as to its etiology, it would seem generally accepted that hormones play a role, which would explain the high frequency of this disorder among older and postmenopausal women. The objective of this study is to demonstrate the benefit of HFI diagnosis for identifying individuals (estimating their age and determining their sex) in the archeo‐anthropological analysis of ancient cremation burial sites and in medicolegal investigations on burned human remains. Our sample consisted of 82 cremated individuals from the Roman Porta Nocera necropolis in Pompeii (1st century BC–1st century AD). After excluding juveniles under 15 years of age, as HFI primarily affects adult individuals, our sample was reduced to 71 individuals, and the prevalence of HFI was 15.5% ( n  = 11). A statistically significant difference is observed between women and men, and no individuals previously identified as male displayed HFI. Furthermore, 90.9% of the individuals displayed degenerative conditions in conjunction with HFI, showing a highly significant correlation of this lesion with signs of aging (chi‐square 9.365; p  = 0.01). Finally, this disorder boosted diagnostic performance in respect of determining sex, increasing the number of biologically sexed individuals from 46.5% to 53.5%. Therefore, we propose that the HFI diagnosis offers genuine added value in the identification of burned human remains.